PENGARUH PENAMBAHAN CREMOPHOR EL TERHADAP PENINGKATAN LAJU DISOLUSI TABLET SIMVASTATIN - Gustaman, Firman (Journal of Pharmacopolium, 2019)
Simvastatin is a statin drug that used to reduce cholesterol levels via inhibition of the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase. The purpose of this study is to determine the effect of Cremophor EL to the dissolution rate of simvastatin tablet. The experiment was consist of  four formula with different concentration of Cremophor EL that were 0%, 0,3%, 0,6% and 0,9%. Preparation of simvastatin tablets was done by wet granulation method. The granules obtained were tested (moisture content, compressibility, flow rate, rest angle and hausner number), physical test of tablets (weight uniformity, hardness, brittleness and crushed time) and dissolution test. Dissolution Apparatus II  was used to dissolution test with 900 mL of phosphate buffer (sodium dihydrogen phosphate and sodium dodecyl sulphate) pH 7.0 as dissolution medium, it was inserted in dissolution vessel at 37 ± 0,50C with 50 rpm. Spectrofotometry uv-vis was used for determination of dissolution result at 238 nm of wavelength. The dissolution test results of simvastatin tablet shows that the addition of 0,6% Cremophor EL in formula 3 has the largest simvastatin dissolution rate.  Keywords: Cremophor EL, Dissolution, Simvastatin,